Операция порождения корневых функционалов и корневые полиномы - Сейфуллин, Т.Р. (Видавничий дім "Академперіодика" НАН України, 2007)
For a system of (n – 1) polynomials in n variables, we consider the connection of the operation of generation for the root functionals with root polynomials.